Is adding resources always beneficial? Multiplicative impact of psychological capital and goal-oriented climate on Spanish public worker satisfaction and engagement - Díaz-Fúnez, Pedro Antonio; Cardella, Giuseppina María; Hernández-Sánchez, Brizeida Raquel; Sánchez-García, José Carlos; Mañas-Rodríguez, Miguel Ángel (Frontiers in Psychology, 2024)
Introduction: The motivation process from personal resources to commitment of administrative employees is still little studied. This article uses the Job Demands-Resources model to investigate how the multiplicative effect of personal resources and a goal-oriented climate among public employees influences their satisfaction and engagement at work. Specifically, it proposes a model where the influence of psychological capital on engagement is mediated by job satisfaction and moderated by the goal orientation climate.Method: A total of 326 employees of the administrative staff of a Spanish Public Administration answered a self-reported survey. Partial Least Square-Structural Equation Modelling (PLS-SEM) approach was used to evaluate the validity and reliability of the data, as well as, to test the hypotheses formulated.Results: The SEM results show the positive impact of psychological capital on employee engagement, and the mediating role of job satisfaction in this relationship. Furthermore, the existence of a goal-oriented climate negatively moderated the relationship between Psychological Capital and Job Satisfaction, reducing the mediation effect. Discussion: These findings open new doors for future research in the necessary adaptation of human resource policies to improve the motivation process in the public administration context.